Peran Environmental Performance dan Green Accounting Sebagai Moderasi Pengaruh Profitabilitas dan Dewan Komisaris Terhadap CSR Utk Mensupport CoP - Tandry Hakki; Helen Chiputri; Yolanda Yolanda (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Each country included in the CoP gathers to conduct a review related to the United Nations Framework Convention on Climate Change, or UNFCCC, which is a major UN treaty. The major UN treaty states that countries need to come together to find out how to stop global warming. The COP has the main task of reviewing each country's targets related to proposed emissions. The implementation of the COP will rotate between five UN regions, namely Africa, Asia, Latin America and the Caribbean, Central and Eastern Europe and Western Europe and others. In its 26th event, the COP has four focus issues of discussion including the importance of switching to electric vehicles, ending deforestation with financial assistance, drafting rules for the global carbon market, and mobilizing funds for developing countries. This study aims to analyze the effect of profitability on CSR Disclosure, the influence of the board of commissioners on CSR disclosure, the role of Environmental performance as a moderation of the influence of profitability on CSR Disclosure, the role of Green Accounting as a moderation of the influence of profitability on CSR Disclosure, the role of Environmental performance as a moderation of the influence of the board of commissioners on CSR Disclosure and the role of Green Accounting as a moderation of the influence of the board of commissioners on CSR Disclosure. This study took the research population from financial sector companies listed on the Indonesia Stock Exchange for the period 2019-2022. Based on the results of this study, it shows that Profitability has a significant effect on CSR Disclosure, the Board of Commissioners does not affect CSR Disclosure, Environmental Performance strengthens the effect of Profitability on CSR Disclosure, Green Accounting does not strengthen the effect of Profitability on CSR Disclosure. Environmental Performance does not strengthen the effect of the Board of Commissioners on CSR Disclosure. Green Accounting does not strengthen the effect of the Board of Commissioners on CSR Disclosure